2012
DOI: 10.3390/w4020460
|View full text |Cite
|
Sign up to set email alerts
|

Scenario Analysis of Nutrient Removal from Municipal Wastewater by Microalgal Biofilms

Abstract: Microalgae can be used for the treatment of municipal wastewater. The application of microalgal biofilms in wastewater treatment systems seems attractive, being able to remove nitrogen, phosphorus and COD from wastewater at a short hydraulic retention time. This study therefore investigates the area requirement, achieved effluent concentrations and biomass production of a hypothetical large-scale microalgal biofilm system treating municipal wastewater. Three scenarios were defined: using microalgal biofilms: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 35 publications
(48 reference statements)
1
27
1
Order By: Relevance
“…The insufficient supply of CO 2 limits algal biomass production because of the unfavourable C:N:P ratio in wastewater [74], but it has been shown that specific aeration and the addition of CO 2 can enhance biomass productivity and removal rates of undesired water constituents. The addition of N or P is sometimes used to ensure molar ratios of nutrients for optimal algal growth [75,76], and co-cultivation with bacteria can be favourable in relation to heterotrophic oxidation of organic compounds in wastewater by microorganisms that benefit from increased oxygen levels, induced by photoautotrophic algal growth [77][78][79]. The removal efficiency of total N and P by microalgae from wastewater has been determined to be between 10 and 97% and is highly dependent on culture mode, tank size, type of wastewater, and the microalgae strain [72,[80][81][82][83], indicating that there is no single technology/species combination that is able to fulfil every WWT goal.…”
Section: Suspended Wwt Systemsmentioning
confidence: 99%
“…The insufficient supply of CO 2 limits algal biomass production because of the unfavourable C:N:P ratio in wastewater [74], but it has been shown that specific aeration and the addition of CO 2 can enhance biomass productivity and removal rates of undesired water constituents. The addition of N or P is sometimes used to ensure molar ratios of nutrients for optimal algal growth [75,76], and co-cultivation with bacteria can be favourable in relation to heterotrophic oxidation of organic compounds in wastewater by microorganisms that benefit from increased oxygen levels, induced by photoautotrophic algal growth [77][78][79]. The removal efficiency of total N and P by microalgae from wastewater has been determined to be between 10 and 97% and is highly dependent on culture mode, tank size, type of wastewater, and the microalgae strain [72,[80][81][82][83], indicating that there is no single technology/species combination that is able to fulfil every WWT goal.…”
Section: Suspended Wwt Systemsmentioning
confidence: 99%
“…More research is currently done in this field [29,30]. In case of extracellular products [31] or in application of wastewater treatment [32] the cells can remain on the surface. For the recovery of intracellular products or biomass the cells can, for example, be harvested by scratching off the surface [33,34].…”
Section: Cell Properties Support Overall Process Performancementioning
confidence: 99%
“…The selected MWWTP at Kashima, has an average of primary treated effluent about 877 m 3 d −1 and has been estimated capable of supplying water (and nutrients) for microalgae cultivation of more than 1 ha size. The available organic components were critical for the initial nutrient balance for integrated wastewater treatment with microalgae cultivation ponds [32,33]. We found that the average daily TN and TP concentration from the existing sewage treatment plant at Minami-soma were 42.7 mg L −1 and 5.8 mg L −1 , respectively.…”
Section: Cultivation Pond Sectionmentioning
confidence: 90%